Significance of manganese fertilization in wheat-based cropping systems of Indo-Gangetic Plain (IGP) - NARENDER NARENDER; R S MALIK; ABIR DEY; M C MEENA (The Indian Journal of Agricultural Sciences, 2018)
Manganese (Mn) is an essential micronutrient, having critical role in plant nutrition. The Mn is component of several enzymes involved in photosynthesis and other physiological processes. The intensive cultivation of rice-wheat (RW) followed since long times, along with induction of rice in non-rice growing areas, especially in north-western Indo Gangetic Plain (NW-IGP) had led to emergence of Mn deficiency, particularly in wheat crops in RW rotation. Higher leaching losses of soil Mn under submerged rice induces Mn deficiency in the subsequent wheat crops. This paper critically assesses the literature on role of Mn on crop growth, distribution of soil Mn and its dynamics, effect of different soil characteristics on soil Mn availability under different cropping systems prevalent in IGP. Soil ionic composition, moisture status, organic matter status, soil pH, cation exchange capacity are some of the soil parameters dictating Mn dynamics in soil. Higher availability of soil Mn was reported under acidic condition, which decreased with increase in soil pH. Literature suggests positive effects of nitrate and phosphates on soil Mn dynamics and crop yields, whereas bicarbonate and chloride application have negative effects. Plant available Mn or DTPA-Mn varied under different cropping systems showing lower availability under RW system. Fractionation studies showed that labile pools of Mn contribute very less towards total soil Mn, leaving large proportion of soil Mn non-labile in nature, thus unavailable for plant uptake. The release of Mn from soil adsorption sites varied under different cropping systems, modifying Mn supply capacity of soil. Maximum release of Mn was found under frequently irrigated sugarcanesugarcane cropping system. Such information are essentially required for developing efficient Mn fertilization scheduling to improve the yield and quality of crops in IGPs.